Physical Education Teacher Teaching Skill Training and Sports MI Mambaul Ma, Arif NU Kerembung Sidoarjo - Sunanto; Pance Mariati; Muchamad Samsul Huda; Hamdiana (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2022)
Of the obtained in understanding the physical and sports education said teachers are different learning and precise account the process will berubah.metode who conducted in the she is a model training and delivery, do matter a, integration and sharing season used to gain knowledge and innovation empirically or teachers in her had she died from the pengamatan.hasil assistance devotion explained the dynamics of mentoring process covering activities implemented, and; forms the technical or stunt the program to solve a problem teachers sports and education olahraga.sedangkan discussion devotion teoritik covering thediscussion of relevance to findings the results of the assistance.